The Influence of Learning Facilities and Motivation on Achievement Study Student Class X in Christian Vocational School in Tombatu - Lumapow, Harold R; Sumual, Shelty D.M.; Tuerah, Philotheus E A; Kambu, Kornelius; Sauyai, Stanly F M; Ratumbuisang, Keith F (JR Education, 2024)
This research aimed to determine whether or not there was an influence of learning facilities and motivation on the learning achievements of students in class X TJK, X Nursing Assistant, X AKL, and X ATPH (30 respondents). The results of this research show that the multiple linear regression analysis obtained the equation Y=80.501 + 0.007x1 + 0.048x2. Where learning facilities and motivation influence the learning achievements of class X students at Tombatu Christian Vocational School. The correlation results show a value of r = 0.241, proving that the influence of learning facilities and motivation on learning achievement is relatively strong. Then for the F test, Fcount = 4,296 > Ftable = 3.35. The results obtained state that there is a significant influence on learning facilities and motivation on the learning achievements of class X students at SNK Tombatu Christian. The influence of learning facilities (x1) and student motivation (x2) influences learning achievements (Y) by 24%, the remainder is influenced by other factors. This research concludes that learning facilities and motivation influence the learning achievements of class X students at Tombatu Christian Vocational School, both simultaneously and partially.